(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Less than a year before of the withdrawal of US and ISAF forces from Afghanistan and in the middle of an ongoing peace process with the Taliban that is not fully taking off, this paper provides insight into Pakistan’s interests in its neighbour and its capacity for influence on the future of the region. Additionally, the paper will examine the state of the peace process in Afghanistan, as well as its future prospects, accounting for the interests of the different actors involved